Uncommon Urinary Actinomycosis Mimicking Upper Urinary Tract Urothelial Tumor: Case Report and Literature Review - Patricia A. Meza-Meneses; Rodrigo Pérez Becerra; Gerardo Garza Sainz; Luis Trujillo Ortiz; Adrián Martinez Correa; Alan Rodrigo Pérez Soriano; Ruben Miguel Angel Santiago González; Aarón Delgado Corral; Omar Vieyra Valdez; Genaro Argüelles Morales; Mario Alberto Toledo Díaz; Alberto Saldivar Luna; et al. (Microorganisms)
Urinary actinomycosis is a rare condition, often mimicking a urinary tract tumor. Due to its low prevalence, it can be challenging to diagnose and may be mistaken for malignancies. A 33-year-old female patient with a history of type 2 Diabetes Mellitus and recurrent urinary tract infections presented to the emergency room with right renal fossa pain radiating to the right hypochondrium, fever with chills, nausea, and vomiting. Physical examination revealed a positive Giordano sign and tenderness at the ipsilateral middle and upper ureteral points. A contrast-enhanced CT scan showed a mass infiltrating the distal third of the right ureter, causing retrograde dilatation and hydronephrosis. Additionally, a liver injury with both liquid and solid components was observed. Therefore, given the suspicion of a urothelial tumor, a diagnostic cystoscopy and ureteroscopy were performed. Using interventional radiology, an abscessed liver lesion was drained, yielding purulent fluid. The histopathological examination revealed no evidence of malignancy. However, due to the strong suspicion of upper urinary tract urothelial carcinoma, a right radical nephroureterectomy with bladder cuff excision and retroperitoneal lymphadenectomy was performed. Histopathological examination ultimately confirmed urinary actinomycosis. Consequently, antibiotic therapy with oral amoxicillin 2 g every 12 h was initiated, leading to a good clinical response. Despite its low incidence, urinary actinomycosis should be considered as a differential diagnosis in cases suspected of urothelial tumors in the upper urinary tract. Increased awareness of this rare condition may help prevent unnecessary surgical interventions.